Beneficial effect of DASH diet combined with regular physical activity on fat mass, anthropometric and metabolic parameters in people with overweight and obesity. DATASET - Soroń, Małgorzata; Więch, Paweł; Dąbrowski, Mariusz (My University, 2023)
Abstract Introduction. Obesity and overweight prevalence has reached pandemic level and became a growing health-related issue worldwide. Excess of fat mass is associated with increased risk of cardiovascular disease, diabetes, musculoskeletal disorders, neuropsychological disturbances, cancer and premature death. The aim of our study was to assess the effect of DASH diet combined with regular physical activity on fat mass, anthropometric and metabolic parameters in overweight and obese subjects. Methods. One hundred people (85 women) with overweight and obesity were included in the study. Mean age of study participants was 48.8±12.1 years and half of them had hypertension. In all study participants anthropometric measurements and laboratory tests were assessed and anthropometric as well as metabolic indices were calculated at baseline and after three months of treatment. Results. A significant decrease in body weight, BMI, waist circumference, fat mass, uric acid level and metabolic indices as well as significant improvement in lipid profile with exception of HDL cholesterol level were found. The effect of DASH diet and physical activity was beneficial irrespective of age, gender and baseline presence of hypertension. Conclusion. Implementation of healthy lifestyle was associated with significant improvement in anthropometric and metabolic parameters. It seems necessary to increase the public awareness of the role of behavioral changes to improve the health-related outcomes.
Keywords: Obesity; DASH diet; physical activity; anthropometric parameters; metabolic parameters.